International review of hydrobiology (Wiley-VCH Verlag Berlin, 1998)
This journal covers the analysis and assessment of biological structures in water in their interconnection with the internal and external cycle of materials.
Keywords: Limnology : Periodicals; Marine biology : Periodicals; Aquatic biology : Periodicals; Freshwater biology : Periodicals; Hydrography : Periodicals; Biologie marine : Périodiques; Limnologie : Périodiques; Hydrobiologie : Périodiques; Biologie d'eau douce : Périodiques